A review of the role of MRI in diagnosis and treatment of early stage lung cancer. (September 2020) - Sim, Austin J.; Kaza, Evangelia; Singer, Lisa; Rosenberg, Stephen A.
Highlights: Better MRI sequences and technology increase its utility in early stage lung cancer. MRI can also provide functional data to aid in diagnosis and response evaluation. MRI-guidance can improve radiotherapy in lung cancer despite physical challenges. Real-time tracking and better soft tissue contrast also facilitate adaptive therapy. Abstract: Despite magnetic resonance imaging (MRI) being a mainstay in the oncologic care for many disease sites, it has not routinely been used in early lung cancer diagnosis, staging, and treatment. While MRI provides improved soft tissue contrast compared to computed tomography (CT), an advantage in multiple organs, the physical properties of the lungs and mediastinum create unique challenges for lung MRI. Although multi-detector CT remains the gold standard for lung imaging, advances in MRI technology have led to its increased clinical relevance in evaluating early stage lung cancer. Even though positron emission tomography is used more frequently in this context, functional MR imaging, including diffusion-weighted MRI and dynamic contrast-enhanced MRI, are emerging as useful modalities for both diagnosis and evaluation of treatment response for lung cancer. In parallel with these advances, the development of combined MRI and linear accelerator devices (MR-linacs), has spurred the integration of MRI into radiation treatment delivery in the form of MR-guided radiotherapy (MRgRT). Despite challenges for MRgRT in early stage lung cancer radiotherapy, early data utilizing MR-linacs shows potential for the treatment of early lung cancer. In both diagnosis and treatment, MRI is a promising modality for imaging early lung cancer.